Determination of microbiological characteristics in the digestive tract of different ruminant species. Issue 6 (25th December 2018) - Zhang, Tian; Mu, Yingyu; Zhang, Deqing; Lin, Xueyan; Wang, Zhonghua; Hou, Qiuling; Wang, Yun; Hu, Zhiyong
Abstract: Holstein dairy cows, Chinese Luxi Yellow cattle, Chinese Laoshan dairy goats, and Chinese Bohai Black cattle were selected for the study. The 16S rDNA sequencing technique was used to analyze the microflora in the digestive tract. The rumen flora in high milk‐yield Holstein dairy cows showed significantly higher proportions of Treponema, Butyrivibrio, Coprococcus, Shuttleworthia, Lachnospira, and Selenomon as, compared with the rumen flora in Chinese Bohai Black cattle and Chinese Luxi Yellow cattle ( p  < 0.05). In addition, the abundances of Succiniclasticum, Ruminococcus, and Fibrobacter in the rumen fluid of high‐yield dairy cows were significantly higher than those in rumen flora of dairy goats. Compared with ruminal flora in Chinese Luxi Yellow cattle, the rumen flora in high‐yield dairy cattle showed significantly higher Prevotella . Compared with the rumen flora in Chinese Laoshan dairy goats, Chinese Bohai Black cattle, and Chinese Luxi Yellow cattle, the flora in high‐yielding dairy cows showed significantly lower proportions of CF231, 02d06, Oscillospira, RFN20, Desulfovibrio, Methanobrevibacter, and SHD‐231. In addition, compared with the rumen flora in dairy goats, the rumen flora in high‐yielding dairy cattle displayed significantly lower proportion of Enterococcus . Compared with the rumen flora in Chinese Bohai Black cattle, the flora in high‐yielding dairy cattle exhibited significantly lower Ruminococcus, YRC22, Pseudobutyrivibrio, L7A_E11, BF311, p‐75‐a5, and Dehalobacterium . Compared with the rumen flora in Chinese Luxi Yellow cattle, the flora in the high‐yield dairy cows also displayed significantly lower proportions of Ruminococcus, YRC22, BF311, Paludibacter, and Dehalobacterium . Abstract : In this study, Holstein dairy cows, Chinese Luxi Yellow cattle, Chinese Laoshan dairy goats and Chinese Bohai Black cattle were selectd as the research object. The 16 SrDNA sequencing technique was used to analyze the microflora in the digestive tract.